(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
Today the theme of the process of planning and design of the expansion and regulation of the cemeteries gains importance due to demographic factors. The goal of the research is the improvement of the contemporary process of planning and design of the public space in order to to frame the possibilities of improvement of the standard practice. The research analyses the planning and design process of the cemetery of the Municipality of Baška, as a characteristic example of this typology in the Croatian coastal area.